1987
DOI: 10.1128/aac.31.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of porins in outer membrane of Proteus, Morganella, and Providencia spp. and their role in outer membrane permeation of beta-lactams

Abstract: Proteus mirabiis, Proteus vulgaris, MorganeUa morganii, Providencia rettgeri, and Providencia alcalifaciens, which were once classified into the same genus, Proteus, were studied. Cefoxitin-resistant mutants from these species were isolated, and it was confirmed that the resistance was attributed to the lack of an outer membrane protein, resulting in a significant decrease in the penetration of hydrophilic cephalosporins through the outer membrane. Comparison of the mutant strains with their parental strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
1
25
2
1
Order By: Relevance
“…(Tables 2 and 3). This was in contrast to results for E. coli and other members of the family Enterobacteriaceae in which porin-deficient mutants were 8-to 32-fold more resistant to certain antibiotics (4,7,17,20,23 (Table 3). This dichotomy in levels of increase in resistance to P-lactam antibiotics of porin-deficient E. coli strains (i.e., large versus small increases) has been previously noted by other researchers (7,17).…”
Section: Methodscontrasting
confidence: 51%
See 1 more Smart Citation
“…(Tables 2 and 3). This was in contrast to results for E. coli and other members of the family Enterobacteriaceae in which porin-deficient mutants were 8-to 32-fold more resistant to certain antibiotics (4,7,17,20,23 (Table 3). This dichotomy in levels of increase in resistance to P-lactam antibiotics of porin-deficient E. coli strains (i.e., large versus small increases) has been previously noted by other researchers (7,17).…”
Section: Methodscontrasting
confidence: 51%
“…A role for some porins in antibiotic uptake has been proposed. This proposal is based largely on observations, in strains of the family Enterobacteriaceae, showing that cells lacking porin proteins in their outer membranes were more resistant than wild-type strains to hydrophilic antibiotics, particularly P-lactams (7,17,18,20,23). However, for some of the more recently introduced P-lactams, there is still some dispute, based on similar studies, as to the role of Escherichia coli porins in their uptake across the outer membrane (7,17)..…”
mentioning
confidence: 99%
“…Biochemical studies of porins from Proteus vulgaris, Proteus mirabilis, Morganella morganii, Providencia rettgeri, and Providencia alcalifaciens suggested that each of these species produced predominantly a single porin with a subunit size of around 35 to 37 kDa (422). Proteoliposome swelling studies showed pore sizes similar to that in E. coli porins, and the channels favored more hydrophilic members among cephalosporins, just as in E. coli (462).…”
Section: Other Porinsmentioning
confidence: 95%
“…In an extensive study in 1987 (308), it was shown that two major OM proteins (presumably porins) are produced in Proteus mirabilis, Proteus vulgaris, Morganella morganii, Providencia rettgeri, and Providencia alcalifaciens and that the major porin in every case had channel properties similar to those of E. coli OmpF. Furthermore, in vitro selection with cefoxitin led to the isolation of mutants deficient in the major porin in each species.…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%